Efficacy of the Single Server Markovian Two-Phase Symmetric Queue with Encouraged Stationary-Queue-Size Analysis (Contemporary Mathematics, 2023)
The efficacy of the Markovian single server symmetric queue is examined in this paper together with the suggested encouraged stationary queue-size analysis. First, we propose the stochastic Markov renewal process with encouraged arrival see time averages and encouraged arrival-stationary-queue-size analysis. The server takes further vacations after two extra service phases or until the server discovers a new set of clients in the service. Finally, we discuss the utility of the Bernoulli two-vacation symmetric queue, and it is clearly shown that the degree of efficiency rises when the encouraged arrival is taken into account.
Keywords: encouraged arrival, stochastic Markov renewal process, vacation time, Bernoulli two vacation symmetric queue